Kidney Transplant Outcomes in Recurrent Versus De Novo IgA Nephropathy - Mark Haas; James Mirocha; Hae Yoon Grace Choung; Jean Hou; Mercury Y. Lin; Michifumi Yamashita; Cynthia C. Nast (Kidney International Reports)
Introduction: IgA nephropathy (IgAN) recurs frequently in kidney transplants, although the reported frequency of recurrence varies because many studies do not distinguish recurrent IgAN from IgAN occurring de novo in the allograft. In addition, there are only limited studies of graft outcomes in patients with recurrent IgAN. Methods: We retrospectively examined 264 kidney transplant biopsies with glomerular IgA deposits, distinguishing whenever possible recurrent versus de novo IgAN, and compared clinical and pathologic features of biopsies of patients within these groups. We also examined graft outcomes in patients with available follow-up to identify findings associated with graft survival. Results: A significantly greater fraction of biopsies with recurrent disease (n = 127) had mesangial (M1) and endocapillary (E1) hypercellularity, crescents (C1-2), and > 1+ (0–4+ scale) glomerular C3 staining than biopsies with de novo (n = 46) IgAN; there was no significant difference between these groups with respect to Oxford S and T scores, or mean time posttransplantation of the biopsy. None of 19 biopsies with IgA deposits attributable to the donor had any MEST-C scores > 0 or C3 staining > 1+. Of 54 patients with recurrent IgAN and follow-up, 25 lost their grafts between 2 and 109 months postbiopsy. Findings at the time of biopsy significantly associated with an increased risk of graft loss in patients were higher serum creatinine (SCr) and proteinuria; Oxford E, T, and C scores > 0; and C3 > 1+. Conclusion: The findings indicate the importance of measuring proteinuria in patients with suspected recurrent IgAN and scoring such biopsies using the Oxford MEST-C scores.